TRANSFORMASI SALURAN POLITIK ETNIS TIONGHOA DI PROVINSI SUMATERA UTARA PASCA ORDE BARU - Rudi Salam Sinaga (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
General elections (elections) that took place in the post-new order era (1999-2014) with various changes to the electoral system and the results of the elections have presented a different geopolitical situation than before. This condition resulted in a